The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1029/2017jb014972
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Earthquake Clustering in Relation to Hydraulic Activities at Geothermal Fields in California

Abstract: Earthquake clustering properties are investigated in relation to fluid balance H(t) (the difference of fluid injection and production rates) using about nine years of data from The Geysers (both the entire field and a local subset), Coso, and Salton Sea geothermal fields in California. Individual earthquake clusters are identified and classified using the nearest-neighbor approach of Zaliapin and Ben-Zion (2013a, https://doi. org/10.1785/0120150211, 2013b, https://doi.org/10.1093/gji/ggw300). These are used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 52 publications
2
45
0
Order By: Relevance
“…Several studies have derived a possible correlation between injection/extraction rates and background seismicity rates of humaninduced seismicity (Llenos & Michael 2013;Johnson et al 2016;Trugman et al 2016;Martínez-Garzón et al 2018). A similar correlation between the rates of induced seismicity and the rates of gas extraction have been observed for the Groningen gas field (Muntendam-Bos & De Waal 2013;De Waal et al 2015;Nepveu et al 2016;Muntendam-Bos et al 2017;Sijacic et al 2017).…”
Section: Gas Production and (Background) Seismicity Ratesmentioning
confidence: 56%
“…Several studies have derived a possible correlation between injection/extraction rates and background seismicity rates of humaninduced seismicity (Llenos & Michael 2013;Johnson et al 2016;Trugman et al 2016;Martínez-Garzón et al 2018). A similar correlation between the rates of induced seismicity and the rates of gas extraction have been observed for the Groningen gas field (Muntendam-Bos & De Waal 2013;De Waal et al 2015;Nepveu et al 2016;Muntendam-Bos et al 2017;Sijacic et al 2017).…”
Section: Gas Production and (Background) Seismicity Ratesmentioning
confidence: 56%
“…Swarms occur generally in areas with elevated fluid‐temperature conditions and low effective viscosity, whereas classical mainshock‐aftershock sequences tend to occur in relatively cold high viscosity regions (Ben‐Zion & Lyakhovsky, ; Zaliapin & Ben‐Zion, ). Oil and gas production, exploration of geothermal energy, and other anthropogenic activities can also lead to and modify observed forms of earthquake clustering (e.g., Ellsworth, ; Goebel & Brodsky, ; Martínez‐Garzón et al, ; Schoenball et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The problem of detecting earthquake clusters (which is different from although closely related to declustering) was shown recently to be effectively addressed by a nearest‐neighbor analysis in space‐time‐magnitude domain (Zaliapin et al, ; Zaliapin and Ben‐Zion, , , , , ). This cluster identification methodology is effective in diverse settings, including tectonic seismicity (Gentili et al, , ; Gu et al, ; Kossobokov & Nekrasova, ; Moradpour et al, ; Peresan & Gentili, ; Reverso et al, ; Ruhl et al, ; Trugman et al, ; Zaliapin et al, ; Zaliapin & Ben‐Zion, , , ), induced earthquakes (Goebel et al, ; Martínez‐Garzón et al, ; Schoenball et al, ; Schoenball & Ellsworth, ; Teng & Baker, ; Vasylkivska & Huerta, ; Zaliapin & Ben‐Zion, ), synthetic seismicity in Epidemic Type Aftershock Sequence (ETAS) models (Gu et al, ; Zaliapin et al, ; Zaliapin & Ben‐Zion, ), and laboratory rock fracture experiments (Davidsen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although seismicity at The Geysers strongly correlate with injection rate and volume, we did not see a strong dependence between the seismic productivity of a main shock and the injected volume around its time of occurrence here (Figure ). Similarly, Martínez‐Garzón et al () using cluster analysis found that at The Geysers the number of aftershocks only partly correlates with the injection rates of the field, with the relation varying significantly with time and no continuous trend found.…”
Section: Discussionmentioning
confidence: 89%